Outcome Measurements Following Total Knee Arthroplasty - Amarase, MD, Chavarin; Tanavalee, MD, Aree; Veerasethsiri, MD, Pathomporn; Ngarmukos, MD, Srihatach (Journal of Southeast Asian Orthopaedics, 2022)
Total knee arthroplasty (TKA) is a definite surgical treatment for late stage knee osteoarthritis. Currently, there are several outcome measurements following TKA which evaluate clinical signs and symptoms, functional activities, and postoperative radiographs. Patient-based evaluation with disease-specific assessment is simple while it provides good validity and reliability. Regarding patient-based evaluations with general health assessment, the short-form health survey (SF)-12 is less time consuming than the SF-36, while providing similar validity and reliability. Although the surgeon-based evaluation is still commonly used in outcome measurement following TKA, it has less responsiveness on the function subscale. Functional performance-based evaluation may not be a sufficient measurement at the immediate-term (< 3 months) follow up, as studies have shown poor improved function performance. However, to perform functional performance[1]based evaluation, the time-up-and-go test or 30-s chair stand test for performance functional-based evaluation are reliable and less time consuming assessments. On the other hand, the immediate post-surgery use of the 6- minute walk distance is somewhat questionable, as it takes a long evaluation time which may cause the patient to become exhausted.